DRILL AND PRACTICE MODEL DALAM PEMBUATAN MEDIA PEMBELAJARAN INTERAKTIF PEMBENTUKAN OBJEK PRIMITIF SEDERHANA DUA DIMENSI - Edi Ismanto; Eka Pandu Cynthia (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2017)
One way to improve the professionalism of teachers is to create a simple interactive learning medium that provides widespread success in a lesson and for its implementation. Computer Graphics is one of the science of the process to produce or create an image based on the description of the object and the background contained in the image using the computer, started from a two-dimensional object that later developed into a three-dimensional object. The simplest primitive object is a two-dimensional object formed from object-forming algorithms in computer graphics. The process and the length of the algorithm is often felt quite difficult for students understanding in the computer lecturing process of this graph, because it is aimed at making a computer graphics learning media with the topic of the formation of two-dimensional object using computer-based learning model drill and practice. This model is chosen because it has advantages: interactive in the presentation of the material, can provide direct feedback, data storage, patience and motivation to learn. Lectora is an e-learning based media development tool, also commonly known as software (authoring tool) software that enables the incorporation of text, image, sound and video elements into an interactive learning multimedia. Lectora software will help the making of interactive learning media in this research, so that with this media, students are expected to more quickly and easily understand the computer lectures graphs especially for material formation of two-dimensional objects.Keywords: Lectora Inspire, Computer Graphics, Learning Media, Two Dimensional Objects.